Nanotechnology-Assisted Isolation and Analysis of Circulating Tumor Cells on Microfluidic Devices - Jie Cheng; Yang Liu; Yang Zhao; Lina Zhang; Lingqian Zhang; Haiyang Mao; Chengjun Huang (Micromachines, 2020)
Circulating tumor cells (CTCs), a type of cancer cell that spreads from primary tumors into human peripheral blood and are considered as a new biomarker of cancer liquid biopsy. It provides the direction for understanding the biology of cancer metastasis and progression. Isolation and analysis of CTCs offer the possibility for early cancer detection and dynamic prognosis monitoring. The extremely low quantity and high heterogeneity of CTCs are the major challenges for the application of CTCs in liquid biopsy. There have been significant research endeavors to develop efficient and reliable approaches to CTC isolation and analysis in the past few decades. With the advancement of microfabrication and nanomaterials, a variety of approaches have now emerged for CTC isolation and analysis on microfluidic platforms combined with nanotechnology. These new approaches show advantages in terms of cell capture efficiency, purity, detection sensitivity and specificity. This review focuses on recent progress in the field of nanotechnology-assisted microfluidics for CTC isolation and detection. Firstly, CTC isolation approaches using nanomaterial-based microfluidic devices are summarized and discussed. The different strategies for CTC release from the devices are specifically outlined. In addition, existing nanotechnology-assisted methods for CTC downstream analysis are summarized. Some perspectives are discussed on the challenges of current methods for CTC studies and promising research directions.